Development of a Portable Data Acquisition System for Extensometry - dos Santos, D. A.; de Souza Soares, A. M. [UNESP]; Tupinambá, W. L.M. [UNESP] (Springer Nature, 2021)
The acquisition and treatment of strain data play an important role in various engineering applications, involving experimental stress analysis on a surface. Its operationalization, however, requires care and equipment that should ensure accuracy in data acquisition and ease of sampling. Deformation data acquisition systems are critical in these cases but still costly when it comes to applications in academic laboratories. This work shows he development of a portable data acquisition system for strain reading using electrical extensometry that can be used to acquire experimental strain data. The developed system has low cost and portability, being suitable to attend data acquisition in remote places. For its development an Arduino UNO R3 board was used in conjunction with an ADS1115 analog-to-digital converter. The converter is required to increase the analog/digital conversion accuracy of the Arduino board and to read electrical voltages in the μV range. In addition, an LCD display was added to the system to show the acquired data instantly. This way, the system does not require the use of a computer to function and can be easily transported. For its measurement, an experiment was carried out with strain gauges glued on the surface of an aluminum beam and connected in a Wheatstone bridge circuit. Also, a numerical model was developed using the LISA finite element program. After testing and comparing experimental, analytical and numerical results, it can be stated that the system was able to acquire data with great precision, reaching its objectives.
Keywords: Arduino; Experimental; Portable data acquisition system; Strain gauges